CROWDFUNDING - A VIABLE ALTERNATIVE TO FINANCE SMALL AND MEDIUM ENTERPRISES - Emilia Cornelia STOICA; Elena Mihaela ILIESCU (Challenges of the Knowledge Society)
The resumption of economic activity after the lockdown imposed by the need to stop the Covid-19 pandemic is a major imperative for any of the states in the world that have faced this scourge. Among the most affected corporate organizations were small and medium-sized enterprises (SMEs), whose small financial resources did not allow them to maintain the level of performance recorded before the pandemic. In order to recover, especially in the context of the economic crisis that is looming at the beginning of 2022, SMEs need even more additional sources of financing and alternative solutions to bank loans would be welcome. In this context, the crowdfunding mechanisms proposed in recent years by the business environment in developed countries and recently adopted in the European Union by "Regulation (EU) 2020/1503 on European providers of crowdfunding services" offer solutions that have proved viable, and a draft law is being prepared in Romania to regulate the crowdfunding of Romanian enterprises.